Optimization of supercritical fluid extraction of polar flavonoids from Robinia pseudoacacia L. heartwood. (April 2023) - Atwi-Ghaddar, Sirine; Destandau, Emilie; Lesellier, Eric
Abstract: The black locust, known as an invasive species, represent many advantages, mainly due to its rapid growth rate and its richness with interesting flavonoids. In this study, supercritical fluid extraction of the two main flavonoids dihydrorobinetin and robinetin, was optimized using a three level Box-Behnken response surface design. The conditions investigated to influence the extraction yield of these flavonoids were temperature (40–80 °C), pressure (10–20 MPa) and modifier's percentage EtOH:H2 O 80:20 (10 %−30 %). The response was quantified using an UHPLC-DAD optimized chromatographic method. The results showed the influence of the extraction conditions on the yield of the molecules of interest. The data were fitted into a second-order polynomial equation, the multiple regression analysis showed a high determination coefficient value (R 2 ) of 0.93. The optimal extraction conditions were 10 MPa, 80 °C and extraction phase composition of CO2 :EtOH:H2 O 80:16:4 for 30 min. These conditions allowed for the recovery 49.2 mg of flavonoids for 1 g of dried wood powder. Graphical Abstract: ga1 Highlights: The biomass produced from the Robinia pseudoacacia L. heartwood can be valorized by flavonoid eco-extraction. Supercritical fluid extraction of polar dihydrorobinetin (DHR) and robinetin (Rob) have been optimized. A Box-Behnken experimental design was achieved with three parameters (P, T, modifier (EtOH/Water) percentage. Rich in flavonoids (around 50 mg/g of dry material) and high-quality extracts were recovered. No selectivity between DHR and Rob yield was noticed with regard to the water %(from 5 to 30 %) in the modifier (20 % in CO2 ).